Seismic images under 60 hotspots: Search for mantle plumes - Zhao, Dapeng (Gondwana research, 2007)
The mantle plume hypothesis is now widely known to explain hotspot volcanoes, but direct evidence for actual plumes is weak, and seismic images are available for only a few hotspots. In this work, we present whole-mantle tomographic images under 60 major hotspots on Earth. The lateral resolution of the tomographic images is about 300 km under the continental hotspots and 400–600 under the oceanic hotspots. Twelve plume-like, continuous low-velocity (low-V) anomalies in both the upper and lower mantle are visible under Hawaii, Tahiti, Louisville, Iceland, Cape Verde, Reunion, Kerguelen, Amsterdam, Afar, Eifel, Hainan, and Cobb hotspots, suggesting that they may be 12 whole-mantle plumes originating from the core–mantle boundary (CMB). Clear upper-mantle low-V anomalies are visible under Easter, Azores, Vema, East Australia, and Erebus hotspots, which may be 5 upper-mantle plumes. A mid-mantle plume may exist under the San Felix hotspot. The active intra-plate volcanoes in Northeast Asia (e.g., Changbai, Wudalianchi, etc.) are related to the stagnant Pacific slab in the mantle transition zone. The Tengchong volcano in Southwest China is related to the subduction of the Burma microplate under the Eurasian plate. Although low-V anomalies are generally visible in some depth range in the mantle under other hotspots, their plume features are not clear, and their origins are still unknown. The 12 whole-mantle plumes show tilted images, suggesting that plumes are not fixed in the mantle but can be deflected by the mantle flow. In most cases, the seismic images under the hotspots are complex, particularly around the mantle transition zone. A thin low-V layer is visible right beneath the 660-km discontinuity under some hotspots, while under a few other hotspots, low-V anomalies spread laterally just above the 660-km discontinuity. These may reflect ponding of plume materials in the top part of the lower mantle or the bottom of the upper mantle. The variety of behaviors of the low-V anomalies under hotspots reflects strong lateral variations in temperature and viscosity of the mantle, which control the generation and ascending of mantle plumes as well as the flow pattern of mantle convection.